PERANCANGAN SISTEM INFORMASI PENJUALAN ONLINE - Sri Rezeki Candra Nursari; Yossela Immanuel (CCIT Journal, 2018)
Internet technology has proved to be one of the effective and efficient information media in the dissemination of information that can be accessed by anyone, anytime and anywhere. Internet technology has a tremendous effect on commerce or business. Only from home or office space, potential buyers can view the products on the computer screen, access the information, order and pay with the available options. Potential buyers can save time and money because they do not need to come to the store or place of transactions so that from their seats can make a decision quickly. Online transactions can connect sellers and potential buyers directly without being limited by space and time. That means online sales transactions have potential buyers from all over the world. In addition, the company's development is considered a bit slow. Therefore designed an online sales system by using web or internet media with the aim to minimize sales process time with the aim to increase sales volume so that company earnings can increase. In this study the authors use waterfall and observation methods. In the implementation is displayed login and registration process, inputting: product data, product ordering, sales, payments, complaints, testimonials. It can be concluded that this system get information and reports easily. This system also allows consumers to make purchases of desired products. Controlling in recording and data security can be handled properly because each user has their respective passwords and given a menu in accordance with the process to be executed. Website visitors who do not register as consumers, can still see the products that are sold and also testimonials that have been made by consumers